Letramentos docentes : com a palavra o professor de língua portuguesa - Silva, Rute Almeida e (2020)
This thesis is linked to the Linguistic and Literacy Studies Group (UFMT / CNPq) and aims, in general terms, to map the literacies of the Portuguese language teacher in life and at work, in addition to understanding his speeches in dealing with these literacies. To this end, we assume the theoretical contribution of Bakhtin and the Circle ([1920-1924] 2010; [1929] 2017; [1952-1953/1979] 2011; [1974/1979] 2011), which addresses dialogism, and of authors who discuss literacy, Street (1984, 2003, 2006 , 2014), the multi-tools, The New London Group (1996), Rojo (2009, 2012), and Freire's critical literacy (1986, 1987, 1989, 1996). We also support theorists who deal with teacher education and training, such as Nóvoa (1992); Charlot (2000) and Garcia (1999, 2009). The methodological approach is of a mixed nature (CRESWELL, 2007). In data collection, it was applied to the teachers an online questionnaire, composed of 53 questions of multiple choices, closed and open and a submission of files in which they demonstrated some of their projects and activities developed in their classrooms. We also resorted to an oral interview, in order to produce more robust inferences about the reality under study. The research corpus consisted of the objective and subjective responses of 1077 Portuguese teachers from all regions of Brazil. As part of the data, we collected 27 interviews from teachers, one from each state in the country, so that we could better understand their trajectories and literacy practices. We analyzed the statements of the participants, aiming to achieve three specific objectives: (1) To know the literacy practices of LP teachers in life and at work; (2) Identify elements that influenced the formation of their literacies in the paths taken by teachers; (3) Demonstrate the practices developed by teachers in teaching and learning reading and writing. The analysis was made in the light of the Bakhtinian theory that contributed to placing the participants in a more extensive temporality, inserted in the great dialogue. (1) The data show the profile of the teachers, who are mostly women between 30 and 39 years old. Most of them attended graduate school and teach in elementary and high school, in public institutions. The analysis made it possible to observe that contact with academic literacies may be linked to the search for professional development and educational improvement; but it can also be a response to the constant demands for updating it. Continuing to study is a means of demanding more attention from public policies and actions for the teaching profession. The results obtained allowed us to realize that teachers are permanently involved in reading and writing activities, especially in the domestic sphere, where the literacies of the experience are constituted. (2) Regarding the literate constitution, we identified the teacher as a great reference and encourager of reading, which shows his importance as an agent of literacy and further centralizes his social role. (3) Regarding the practices developed in the classroom, we saw that projects for reading, writing and rewriting texts have been prioritized, which may be related to the development of teachers' curricular and practical literacies. At the same time, it was possible to notice inconsistencies in the conduct of activities in the teaching speeches, issues that can significantly reduce the student's experience as a reader and writer. This leads us to ponder about the need for congruences between “what” and “how” is taught in universities, “what” and “how” is taught in schools and “what” and “how” is demanded in assessments in the country.